Porous media : applications in biological systems and biotechnology - Vafai, K. (Kambiz) (CRC Press, 2011)
An exhaustive examination of the applications of porous media modeling to biomedical and biological sciences, this book covers various transport processes, mechanical behavior, and material properties of biological tissues. It illustrates the role of porous media modeling in describing biomedical and biological processes and addressing some of the challenging issues. The book provides a new perspective on and framework for understanding various biomedical and biological phenomena. It contains sophisticated porous media models that can be used to improve the accuracy of modeling in a variety of biomedical applications.